Wild Hogs [videorecording (Blu-Ray)] - Copeland, Brad; Allen, Tim, 1953-; Travolta, John, 1954-; Lawrence, Martin, 1965-; Macy, William H., 1950-; Liotta, Ray; Tomei, Marisa; Durand, Kevin; Gainey, M. C.; Hennessy, Jill, 1968- (Touchstone Home Entertainment, 2007)
Four middle-aged men decide to take a motorcycle road trip from Cincinnati to the Pacific in order to get away from their lives which are leading them nowhere. These "Wild Hogs" tear up the road and eventually stop in New Mexico for a drink, not knowing that the bar belongs to the Del Fuegos, a mean biker gang. When the Del Fuegos steal a bike that belongs to the Wild Hogs, Woody, one the the Hogs decides to steal the bike back. Woody cuts the fuel pipes of the bikes and provokes an accident that explodes the bar, but he does not tell the truth to his friends. When they stop in the small town of Madrid without gas, Dudley falls in love for the waitress and owner of the local bar Maggie. The Del Fuegos pursue the Hogs and trap them in the town.